Penerapan Metode Kitabah terhadap Kemampuan Menghafal Al-Qur'an Juz 'Amma - Sari, Dewi Asri Fatma (Journal of Transdisciplinary Studies in Religion and Education, 2025)
MI Miftahul Ulum is an elementary madrasah that prioritizes tahfidz education with the target of memorizing Juz ‘Amma of the Qur'an for each graduate. Teaching Qur’an memorization is a challenge that requires the right method, so this study examines the application of the Kitabah method by tartil teachers at MI Miftahul Ulum Kedungkampil, along with the factors that support and hinder the achievement of student memorization targets. The main objectives are: 1) To reveal the application of the Kitabah method to improve Juz ‘Amma memorization; 2) To identify the supporting and hindering factors. This qualitative study collected data through observation, interviews, and documentation, and analyzed the data through reduction, presentation, and conclusion drawing. The results show that the application of the Kitabah method is effective in improving memorization of Juz 'Amma of the Qur'an. The main supporting factors are student motivation and teacher guidance, while the obstacles include differences in student character and background, limited memorization time, and minimal guidance at home. In conclusion, the Kitabah method is effective in strengthening Al-Qur'an memorization skills, although external obstacles need to be overcome to optimize tahfidz learning in madrasah ibtidaiyah.